Evaluation of the safety and efficacy of TY-51924 in patients with ST elevated acute myocardial infarction – Early phase II first in patient pilot study. Issue 2 (February 2016) - Takayama, Tadateru; Kimura, Kazuo; Fukuzawa, Shigeru; Hirayama, Haruo; Sone, Takahito; Ueda, Yasunori; Uematsu, Masaaki; Ishihara, Masaharu; Nakao, Koichi; Matsumoto, Naoya; Kosuge, Masami; Hiro, Takafumi; et al.
Abstract: Background: In myocardial ischemia–reperfusion injuries, the involvement of the Na + /H + exchanger (NHE) is considered to be one of the pathogenic mechanisms following reperfusion. TY-51924 is a novel hydrophilic NHE inhibitor with a lower risk of central neurotoxicity than previous NHE inhibitors. This open-label, dose-escalating study was undertaken to investigate the safety, efficacy, and pharmacokinetics of TY-51924 in patients with ST-elevation myocardial infarction (STEMI). Methods: Consent was obtained from a total of 30 patients with first anterior STEMI. After 12 patients were determined to be ineligible, the remaining 18 patients, each of whom was undergoing primary percutaneous coronary intervention (pPCI), received TY-51924 intravenously up to 10, 20, or 30 mg/kg as the low-, medium-, or high-dose groups, respectively ( n = 6 in each group). The primary endpoints were safety (up to 7 days) and plasma drug concentration. The myocardial salvage index (MSI) was measured by 201 Tl/ 123 I-beta-methyl- p -iodophenyl pentadecanoic acid single photon emission computed tomography (SPECT) 3–5 days after pPCI. Results: No side effects were observed. Plasma drug concentrations increased dose-dependently, and were subsequently eliminated rapidly. MSIs were 0.118, 0.335, and 0.192 in the low-, medium-, and high-dose groups, respectively. In additional analysis, the combined MSIs in the medium- and high-dose groups were significantly higher than those in the low-dose group, in patients with a longer time from symptom onset to reperfusion ( p = 0.0247). Conclusions: No side effects were observed even at the highest dose with this novel hydrophilic NHE inhibitor. Therefore, TY-51924 is thought to be safe in patients with STEMI, even at the highest dose. Potential cardioprotective effects of intravenous TY-51924 might be expected based on the results obtained for the MSIs using SPECT at 20–30 mg/kg. However, further large-scale, double-blind, placebo-controlled clinical studies are required to confirm the efficacy and safety implied in the current study.